2016
DOI: 10.1097/j.pain.0000000000000338
|View full text |Cite
|
Sign up to set email alerts
|

Translation of random painful stimuli into numerical responses in fibromyalgia and perioperative patients

Abstract: Number-based assessment tools are used to evaluate pain perception in patients and determine the effect of pain management. The aim of this study was to determine the ability of chronic and acute pain patients to score their response to randomly applied noxious stimuli and assess the effect of opioid treatment. Thirty-seven healthy controls, 30 fibromyalgia patients, and 62 postoperative patients with acute pain received random heat pain (Hp) and electrical pain (Ep) stimuli. All subjects rated their pain on a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 22 publications
0
9
0
Order By: Relevance
“…5). As discussed previously, 11 different pain models activate different pain pathways with differences in central processing.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…5). As discussed previously, 11 different pain models activate different pain pathways with differences in central processing.…”
Section: Discussionmentioning
confidence: 83%
“…After obtaining Pth and Ptol values for electrical and heat tests, we constructed a linear distribution of 8 interpolated currents and temperatures in between Pth and Ptol, corresponding with estimated NRS scores of 2 to 9. 11,12 We then randomly applied stimuli to the subjects corresponding with NRS values 1, 4, 6 and 9 with at least 1-min intervals between stimuli. First one complete set of stimuli (heat or electrical) was applied and followed by a second set after a 30-min pause, the order of which was random.…”
Section: Stimulation Protocolmentioning
confidence: 99%
“…In real life rapid and loose up-and-down titrations are allowed aimed at optimizing effect with as few as possible side effects and often combined with comedication; (4) Pain intensity scores are often not well understood by patients and additionally may not capture the beneficial effects of ketamine on mood, cognition, and quality of life. Linear metric scores on a 100 mm scale or numerical ratings poorly represent the actual perceived pain, particularly under conditions of chronic pain and cognitive impairment [57,58]. Moreover, ketamine may affect cognition and consequently more qualitative than quantitative scoring systems are likely required; (5) Placebo controls may cause a bias in study outcome either due to an inflated placebo effect or due to the fact that well-informed clinical-trial participants that experience absence of side effects may decide to terminate their participation in the study [59,60]; and finally, (6) In real life, patients with severe and progressive neuropathic pain often have other symptoms or complaints that restrict their ability to be included in the trial.…”
Section: Expert Opinionmentioning
confidence: 99%
“…Additionally, patients and caregivers interpret pain intensity scores differently [3]. A recent study showed that some patients are not able to use the NRS reliably [31]. Patients may choose not to take more analgesics because they interpret their pain as “bearable” [12, 32].…”
Section: Discussionmentioning
confidence: 99%